COMPATIBILITY OF FISCAL AND MONETARY POLICIES AND THEIR RELATIONSHIP WITH THE LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article examines the impact of fiscal and monetary policy on the labor market and their coordination. The primary focus is on how fiscal and monetary policies affect macroeconomic stability, including inflation, gross domestic product, and the investment climate.The article discusses scientific research and findings conducted in various countries, analyzing both the direct and indirect effects of fiscal and monetary policies on the labor market. It also contemplates how coordinated fiscal and monetary policies can contribute to economic growth and maintain stability in the labor market.
Keywords: fiscal policy, monetary policy, labor market, investment climate, employment, inflation, stability.